2019
DOI: 10.1093/jnci/djz159
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Tumor-Initiating Cells in Multiple Myeloma

Abstract: Background Treatment failures in cancers, including multiple myeloma (MM), are most likely due to the persistence of a minor population of tumor-initiating cells (TICs), which are noncycling or slowly cycling and very drug resistant. Methods Gene expression profiling and real-time quantitative reverse transcription polymerase chain reaction were employed to define genes differentially expressed between the side-population cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 43 publications
0
41
0
Order By: Relevance
“…Currently, SP analysis is increasingly applied in CSCs research as an indication of stemness [86][87][88] and therapy resistance. 89,90 Noncoding RNAs In recent years, research on noncoding RNAs has become increasingly prominent. Many studies have indicated noncoding RNA can be a CSC marker.…”
Section: Intracellular Markersmentioning
confidence: 99%
“…Currently, SP analysis is increasingly applied in CSCs research as an indication of stemness [86][87][88] and therapy resistance. 89,90 Noncoding RNAs In recent years, research on noncoding RNAs has become increasingly prominent. Many studies have indicated noncoding RNA can be a CSC marker.…”
Section: Intracellular Markersmentioning
confidence: 99%
“…The CD24+ phenotype of CSCs has also been demonstrated in other tumors including cervical cancer, 148,149 cholangiocarcinoma, 150 colorectal cancer, 151 and gastric cancer 152 . A recent study described that TICs in multiple myeloma (MM) were positive for CD24 153 . CD24+ MM cells exhibited increased clonogenicity, drug resistance and tumorigenicity.…”
Section: How Is Cd24 Expression Regulated?mentioning
confidence: 96%
“…Different formats were used for therapy. These included unconjugated mAbs, where the effector mechanism mainly relies on antibody‐dependent cell‐mediated cytotoxicity of SWA11, 153,159 ALB9, 160 antibody‐drug conjugates, 161‐163 bispecific antibodies, 164 chimeric antigen receptor T cells 166 or chimeric antigen receptor‐natural killer cells 165 . In all these experiments more or less efficient killing of tumor target cells was observed in vitro or in vivo in human tumors grafted into immunodeficient mice.…”
Section: How Is Cd24 Expression Regulated?mentioning
confidence: 99%
“…Nonetheless, another study demonstrated that clonotypic CD138 + PCs also have some properties of CSCs such as self-renewal, tumour-initiating potential and drug resistance [237,238]. A more recent study with gene expression profiling of putative CSCs and the main population of MM cells derived from 11 MM patients, identified CD24+ MM cells as being capable of maintaining CSC features of self-renewal and drug resistance [239].…”
Section: Persistence Of Cancer Stem Cellsmentioning
confidence: 99%